Muscular Dystrophy-Dystroglycanopathy and Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2013)
Investigators from the University of Catania, and other centers in Europe have identified a novel genetic glycosylation disorder, DPM2-CDG (part of the DPM synthase complex) in 3 infants with severe hypotonia, progressive muscle weakness and wasting, elevated CK, absent psychomotor development, intractable epilepsy with onset at 1 week to 5 months, and early mortality.